Treatise on Law of Land and Land Revenue - Raghavan, P (Chennai R. Lakshmi Publishers, 2021)
Law of the land has to be such that it enables in reducing the length of time and-owner needs to spend in the courts of law to establish one's own title over piece of land either by inheritance, purchase or partition on land holdings-either in the civil courts or revenue courts as per the prevailing law.
Keywords: Law; Land Revenue; IAS as an author